Intratesticular adenomatoid tumor: A case report and review of the literature - Sameer Al Diffalha, MD; Stefan E. Pambuccian, MD; Ahmer V. Farooq, DO; Güliz A. Barkan, MD (Elsevier, 2016)
Adenomatoid tumors (ATs) are rare benign neoplasms that typically occur in the male and female genital tract. In men, the most common site of ATs is the epididymis and other paratesticular locations (tunica albuginea, spermatic cord, and ejaculatory ducts). However, intratesticular AT is exceedingly rare and may mimic a malignant neoplasm. We report a case of an AT occurring in a 27-year-old man with no prior medical, urologic or trauma history, who presented with right-sided scrotal pain of a few days' duration. Physical examination showed no skin change in the scrotum, a normal-sized, nontender left testis and an enlarged, tender right testis. Ultrasound images of the scrotum showed an eccentric, predominantly hypoechoic vascular mass in the posterior aspect of the right testis measuring 2.2 × 2.1 × 2.1 cm. Tumor markers were within normal limits. His workup was negative for metastatic disease. A right radical orchiectomy was performed. Histological examination and immunohistochemical stains confirmed the diagnosis of adenomatoid tumor confined to the right testis. We report this rare, benign neoplasm of mesothelial origin that more often occurs in a paratesticular location, but rarely has been shown to involve the testicular parenchyma.